Canonic Threads and Large-Scale Structure in Canons - Alan Gosman (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
This article introduces the concept of canonic threads: patterns made of alternating dux and comes notes, in which the notes are separated by the time interval of the canon. Canonic threads are developed using as focus pieces Bach’s Goldberg Variations and Brahms’s Variations on a Theme by Schumann, op. 9. Both sets present a compendium of canonic threads, and demonstrate how threads can integrate a theme’s harmonic and phrase-structural constraints into a variation with strict canonic form. The article also considers various techniques that allow an underlying template of canonic threads to function over a wide range of harmonic and metric possibilities.